THE RELATIONSHIP BETWEEN IMPLEMENTATION ORAL HYGIENE WITH ORAL INFECTION OF PATIENT CVA IN THE FLAMBOYAN ROOM OF LAMONGAN GENERAL HOSPITAL - siti mudrikatin; ASEF WILDAN MUNFADLILA (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
ABSTRACT Introduction: Oral hygiene is the act of maintaining or keeping the oral cavity clean and healthy to prevent caries, periodontal tissue diseases, and bad breath. Oral hygiene in patients affected by CVA is important because it can clean the dirt in the mouth. This study was to determine the relationship between the implementation of oral hygiene with the incidence of infection in the oral cavity in CVA patients in the flamboyant room of RSUD Lamongan in 2018. Method: The study design used was correlational analytic with the purposive sampling approach with data collection methods by means of observation and checklist, the sample of this study was 24 people affected by CVA. The sampling used in this study uses the technique of sampling, total sampling, the independent variable implementation of Oral Hygiene and the dependent variable on the occurrence of oral cavity infections to determine the relationship between variables using the Spearman rank statistical test. Results: Based on the results of the study showed that of the 24 respondents who had an infection of (45.8%) 11 respondents, and half of the respondents who did not have an infection of (54.2%) 13 respondents were measured using the Spearman rank statistical test obtained: 0.045 Conclusion: Efforts made to find out the problem, namely counseling, always add insight to the public who do not know about oral hygiene. Keywords: implementation of oral hygiene, infection of the oral cavity